(untitled) (GIST – Education and Learning Research Journal, 2019)
The purpose of this study is to characterize the assessment process in an English Language Teacher Education Program (ELTEP, hereafter) at a Colombian public university. Following a qualitative-descriptive approach, we identified the perceptions of teachers and students facing this process, reviewed some official documents such as course syllabi and test samples, and observed some classes to respond to the main inquiries of the present study. As data collection instruments we used interviews, questionnaires, field diaries, and documentary records, which allowed for the corresponding triangulation of the information. Once the information was collected, we proceeded to its respective analysis through a methodology of descriptive statistics and qualitative analysis with the support of a computer program for the codification and categorization of information. The results of this study allow us to conclude that in spite of the general guidelines proposed by the institution in terms of assessment of learning, and some good evaluative practices implemented by the teachers of the aforementioned Program, the consolidation of an approach is required. An approach understood as criteria and pedagogical procedures that guide both teachers and students, and one that promotes more formative, fair and democratic assessments.